The Comparison of Stress, Anxiety, Depression, and Academic Achievement Among Orphaned and Non-Orphaned High School Girls - Pargar, Moslem; Torkan, Hajar; Mohammadi Bajgirani , Fatemeh Sadat (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: This research aimed to compare stress, depression, anxiety, and academic achievement between orphaned high school girls and their non-orphaned peers.Methods and Materials: The study employed a causal-comparative design. The sample consisted of 30 orphaned girls who volunteered to participate. The statistical population included all orphaned high school girls in Mobarekeh city. Non-orphaned students were matched with orphaned students. The measurements used were the Bern Stress Scale, Spence Children's Anxiety Scale, Kutcher Depression Scale, and the mean of academic scores. Data were analyzed using descriptive statistics (mean and standard deviation) and inferential statistics (MANCOVA).Findings: The analysis revealed no significant differences between the two groups regarding stress, depression, and anxiety, except for coping with stress by peers and self-stress.Conclusion: Based on these results, it can be concluded that being orphaned does not significantly affect stress, depression, and anxiety levels. However, it does influence peer stress and self-stress among adolescent girls.